Wawasan Kebangsaan Perspektif Islam: Konsepsi Nasionalisme Dalam Al-Qur’an : DOI 10.58569/jies.v2i2.991 - M. Khamim (Pascasarjana Universitas Islam Jakarta, 2024)
Currently, the Indonesian people are quite friendly with conflicts and social problems. Poverty, corruption, weak cultural resilience as well as inter-ethnic conflicts and conflicts in the name of religion are rife as challenges that directly or indirectly affect the size of nationalism and love for the homeland among Indonesian people. As a country with a large Muslim population, Indonesia should be based on Islamic values ​​in the order of life. Islam as a universal religion, has regulated various aspects of human life, including the values ​​of nationalism and love for the homeland. This paper was written as an effort to explore the scientific treasures of the national argument in an Islamic perspective, namely to dig deeper into the relationship between Islam and the spirit of nationalism and love for the homeland. The approach used in this paper is library research. The results of the study indicate that the implicit arguments for nationalism and love for the homeland can be found in the Qur'an and the hadith of the Prophet. Nationalism which is affirmed in the Qur'an is nationalism in the broad sense or the spirit of nationalism. Meanwhile, in the perspective of the Prophet's history, the events leading up to the Prophet's migration and the Medina Charter are a concrete form of nationalism that has been exemplified by the Prophet Muhammad.